Egyptian Food Consumption Survey 2015-2016 - Tawfik, Afaf (2019)
As part of the IFPRI Egypt Seminar in partnership with the National Nutrition Committee: "the 100 million healthy lives initiative: Food availability, access and consumption patterns in Egypt"